A case of adenomatoid odontogenic tumor-like tumor, unusual benign odontogenic tumor in the maxilla. Issue 2 (March 2015) - Kawahara, Kenta; Nakayama, Hideki; Fukuma, Daiki; Nagata, Masashi; Yoshida, Ryoji; Tanaka, Takuya; Nakagawa, Yoshihiro; Hirosue, Akiyuki; Hiraki, Akimitsu; Takeda, Yasunori; Shinohara, Masanori
Abstract Adenomatoid odontogenic tumors (AOTs) are rare, benign odontogenic tumors characterized by a progressively slow growing pattern and asymptomatic behavior. The most common presentation is a cystic mass involving an unerupted tooth (especially canine), and the usual site is the anterior maxillary region. These tumors are histopathologically thought to arise from the odontogenic epithelium with or without inductive changes in the connective tissue. We herein report a rare case of AOT-like tumor arising in the first premolar region to the first molar region of the maxilla. A 33-year-old male was referred to our hospital for further evaluation of a round radiolucent lesion of the maxilla. After performing a biopsy, which confirmed the diagnosis of AOT, surgical excision was performed under general anesthesia. The tumor was encapsulated and relatively large (approximately 30 mm in maximal diameter) for an AOT. Furthermore, an unusual finding of the root resorption of adjacent teeth was observed. The histopathological examination showed duct-like structures composed of regularly single- or double-layered cuboidal cells; however, there were no duct-like structures composed of columnar epithelial cells characteristic of AOT. On the other hand, the existence of melanocytes, ghost cells, and CK19-positive cells suggests that our case was a benign odontogenic tumor. Taking all findings into account, we diagnosed this patient with an AOT-like, benign odontogenic tumor. The patient's postoperative course was uneventful, and no signs of recurrence have been found 2 years after the operation.